2013
DOI: 10.1177/1470320313475908
|View full text |Cite
|
Sign up to set email alerts
|

Dual therapy of vildagliptin and telmisartan on diabetic nephropathy in experimentally induced type 2 diabetes mellitus rats

Abstract: The addition of telmisartan to vildagliptin demonstrated the best control over blood pressure, glycemia and diabetic nephropathy markers, renal structural changes and improvement of renal function as opposed to monotherapy with either drug, possibly because of the dual inhibitory effect on the renin-angiotensin system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…Improvement of the two previously mentioned parameters can be explained in our investigation by the significant increase of plasma active GLP-1 levels detected in the treated group when compared to corresponding value in the correlated non-treated group. These results agree with [57] who explained anti-diabetic hypoglycemic effect of Vildagliptin by improved insulin secretion and peripheral insulin sensitivity through binding covalently to the catalytic site of Sohair A. Saleh, el al.…”
Section: Vildagliptin-treated Groups (Type I and Type Ii)supporting
confidence: 92%
“…Improvement of the two previously mentioned parameters can be explained in our investigation by the significant increase of plasma active GLP-1 levels detected in the treated group when compared to corresponding value in the correlated non-treated group. These results agree with [57] who explained anti-diabetic hypoglycemic effect of Vildagliptin by improved insulin secretion and peripheral insulin sensitivity through binding covalently to the catalytic site of Sohair A. Saleh, el al.…”
Section: Vildagliptin-treated Groups (Type I and Type Ii)supporting
confidence: 92%
“…Some studies revealed an elevation of urea and plasma Cr and reduction of plasma albumin levels in diabetic rats (16,17,19). The results of Sharma et al study indicate that BUN and serum Cr level significantly increased in type 2 diabetic rats (20). Likewise, Viswanathan et al showed a significant serum albumin reduction in type 2 of diabetes (21).…”
Section: Discussionmentioning
confidence: 98%
“…Telmisartan is used mainly due to its effect on RAS, but the effects on activate PPAR-γ has been explored in some studies. According to these studies, PPAR-γ activation appears to be an innovative mechanism to mediate the bene cial effects of inhibitors angiotensin receptors [20,21,34,36].…”
Section: Discussionmentioning
confidence: 99%